DEVELOPMENT OF B2B MARKETING STRATEGY AND SWOT ANALYSIS IN SUPPORTING SDGS - Muhammad Iqbal Alim El Hakim; Imelda Dian Rahmawati (Antis Publisher, 2025)
Objective: This study aims to develop an effective business-to-business (B2B) marketing strategy for Sartika Ratu, a company engaged in the Hajj and Umrah equipment industry. In facing the challenges of declining revenue and market share, this study uses a mixed-method approach with a Sequential Exploratory model to gain an in-depth understanding of the internal and external factors that influence the company's marketing strategy. Method: Data was collected through semi-structured interviews and observations, then analyzed using SWOT analysis involving IFE and EFE matrices. Result: The results show that the company's decline in revenue is related to declining B2B customer loyalty and challenges in attracting new customers. SWOT analysis identifies the company's main strengths in product quality and customization capabilities, while weaknesses are found in ineffective online marketing distribution. Based on these findings, it is recommended that the company develop a product differentiation strategy and improve its digital distribution channels to strengthen its competitive position. Novelty: This study also emphasizes the importance of integrating Sustainable Development Goals (SDGs) principles into marketing strategies, especially in supporting SDGs 8, 9, and 17, highlighting a holistic and data-driven approach that enables Sartika Ratu to increase competitiveness and achieve sustainable long-term growth in the Hajj and Umrah equipment industry.